2001
DOI: 10.1016/s0002-9440(10)61734-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-12 and Stat-4 in the Regulation of Airway Inflammation and Hyperreactivity in Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is a respiratory pathogen that can cause significant morbidity in infants and young children. Interestingly, the majority of children who acquire a RSV infection do not exhibit severe symptoms. Development of a Th1 response has been associated with resolution of symptoms in viral infections and may explain mild RSV illness. The current study investigated the cytokine response observed in mild disease in C57BL/6 mice that had low airway resistance and mucus production with litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 52 publications
3
48
2
Order By: Relevance
“…Previous studies have demonstrated that TLR3 has an integral role for responding to dsRNA (28 -31), a required intermediate for RSV that is a negative strand virus. It is important to note that previous studies have shown that this strain of mouse readily clears RSV and has little associated pathogenic response (27,32,33). The present studies found no significant difference in the TLR3 Ϫ/Ϫ animals' ability to clear RSV, compared with wild-type control mice, examining RSV-specific pulmonary titers during infection (data not shown).…”
Section: Tlr3-deficient Mice Demonstrate Sufficient Viral Clearance Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that TLR3 has an integral role for responding to dsRNA (28 -31), a required intermediate for RSV that is a negative strand virus. It is important to note that previous studies have shown that this strain of mouse readily clears RSV and has little associated pathogenic response (27,32,33). The present studies found no significant difference in the TLR3 Ϫ/Ϫ animals' ability to clear RSV, compared with wild-type control mice, examining RSV-specific pulmonary titers during infection (data not shown).…”
Section: Tlr3-deficient Mice Demonstrate Sufficient Viral Clearance Rmentioning
confidence: 99%
“…Human RSV A strain, originally isolated at University of Michigan Hospitals, was propagated in Hep2 cells as previously described (25)(26)(27). To determine viral titers, a plaque assay was performed in Vero cells that were grown until they were semiconfluent.…”
Section: Rsv Propagation and Titer Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has previously shown that the up-regulation of IL-13 in RSV-infected BALB/c exacerbates mucus production, airway hyperreactivity, and airway inflammation (9 -11), whereas others have indicated that the age of infection can influence the production of IL-13 (12). Conversely, IL-12 in RSV-infected C57BL/6 mice creates a more protective immune environment by limiting mucus overexpression, airway hyperreactivity, and eosinophilia (13). IL-12 is primarily produced by activated APCs in the lung and promotes the development of Th1 immune cells and cell-mediated immunity (14).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…We previously have demonstrated that C57BL/6 mice infected with RSV respond with a more protective immune response and exhibit only mild pathophysiology (13). To test the hypothesis that TLR signaling is critical in generating an appropriate nonpathogenic immune response, we first compared lung inflammation in MyD88 Ϫ/Ϫ and C57BL/6 mice infected with RSV.…”
Section: Myd88 Deficiency Increases Mucus and Th2-mediated Lung Inflamentioning
confidence: 99%